Acetone–butanol–ethanol production from substandard and surplus dates by Egyptian native Clostridium strains. (April 2015) - Abd-Alla, Mohamed Hemida; Zohri, Abdel-Naser Ahmed; El-Enany, Abdel-Wahab Elsadek; Ali, Shimaa Mohamed
Abstract: One hundred and seven mesophilic isolates of Clostridium were isolated from agricultural soils cultivated with different plants in Assuit Governorate, Egypt. Eighty isolates (out of 107) showed the ability to produce ABE (Acetone, butanol and ethanol) on T6 medium ranging from 0.036 to 31.89 g/L. The highest numbers of ABE producing isolates were obtained from soil samples of potato contributing 27 isolates, followed by 18 isolates from wheat and 10 isolates from onion. On the other hand, there were three native isolates that produced ABE more than those produced by the reference isolate Clostridium acetobutylicum ATCC 824 (11.543 g/L). The three isolates were identified based on phenotypic and gene encoding 16S rRNA as Clostridium beijerinckii ASU10 (KF372577 ), Clostridium chauvoei ASU55 (KF372580 ) and Clostridium roseum ASU58 (KF372581 ). The highest ABE level from substandard and surplus dates was produced by C. beijerinckii ASU10 (24.07 g/L) comprising butanol 67.15% (16.16 g/L), acetone 30.73% (7.4 g/L) and ethanol 2.12% (0.51 g/L), while C. roseum ASU58 and C. chauvoei ASU55 produced ABE contributing 20.20 and 13.79 g/L, respectively. ABE production by C. acetobutylicum ATCC 824 was 15.01 g/L. This study proved that the native strains C. beijerinckii ASU10 and C. roseum ASU58 have high competitive efficacy on ABE production from economical substrate as substandard and surplus date fruits. Additionally, using this substrate without any nutritional components is considered to be a commercial substrate for desired ABE production. Highlights: One hundred and seven isolates of Clostridium were isolated from agricultural soils. The major isolates were recovered from soil samples of potato plants. Three native isolates produced ABE more than Clostridium acetobutylicum ATCC 824 on T6 medium. These isolates were identified as Clostridium beijerinckii ASU10, Clostridium chauvoei ASU55 and Clostridium roseum ASU58. The highest ABE level from surplus date fruits was produced by C. beijerinckii ASU10.